2012
DOI: 10.1371/journal.pone.0032114
|View full text |Cite
|
Sign up to set email alerts
|

From Local to Global Dilemmas in Social Networks

Abstract: Social networks affect in such a fundamental way the dynamics of the population they support that the global, population-wide behavior that one observes often bears no relation to the individual processes it stems from. Up to now, linking the global networked dynamics to such individual mechanisms has remained elusive. Here we study the evolution of cooperation in networked populations and let individuals interact via a 2-person Prisoner's Dilemma – a characteristic defection dominant social dilemma of coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 72 publications
6
68
0
Order By: Relevance
“…It has also been shown that structures of social networks can influence the emergence of cooperative behavior (Nowak and May, 1992;Nowak, 2006;Pinheiro et al, 2012), theoretically. Recent experimental studies with interaction networks of human populations based on repeated games suggested that the population structure can affect the evolution of cooperative behavior as theoretically expected (Rand et al, 2014), or may not affect so significantly than theoretically expected (Grujić et al, 2014) because they might adopt different strategy updating criterions (e.g., moody conditional cooperation Grujić et al, 2014, reinforcement learning Horita et al, 2017 rather than an imitation-based criterion (e.g., imitating the best), which is a common assumption in theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that structures of social networks can influence the emergence of cooperative behavior (Nowak and May, 1992;Nowak, 2006;Pinheiro et al, 2012), theoretically. Recent experimental studies with interaction networks of human populations based on repeated games suggested that the population structure can affect the evolution of cooperative behavior as theoretically expected (Rand et al, 2014), or may not affect so significantly than theoretically expected (Grujić et al, 2014) because they might adopt different strategy updating criterions (e.g., moody conditional cooperation Grujić et al, 2014, reinforcement learning Horita et al, 2017 rather than an imitation-based criterion (e.g., imitating the best), which is a common assumption in theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…Popular mechanisms that aim at solving this evolutionary conundrum such as kin selection [17], direct reciprocity [13], [18], voluntary participation [19], [20], reputation [21][24], social structure [25][29], peer and pool punishment [30][40], etc , are able to promote cooperation by transforming a PD into a SH [4], [16], [41], [42]. From a sociological perspective, the SH portrays a milder dilemma when compared to the PD , since it strips temptation from the latter, leaving only fear in the way between individual and collective interest [43], [44].…”
Section: Introductionmentioning
confidence: 99%
“…In the mean-field limit, in which everyone is equally likely to interact with anyone else (also known as well-mixed population approximation), this dilemma inexorably condemns cooperation to extinction [27], a fate which may change when individuals are embedded in a social network represented by means of a graph, in which structural diversity is ubiquitous [1][2][3]5,[7][8][9][10][22][23][24][25][26]28,[30][31][32][33][34][35].…”
mentioning
confidence: 99%
“…Despite the importance of social networks in defining the paths and ends of the dynamical processes they support, showing how important it is to address and understand population dynamics from a complex networks perspective [5,10,32,33,37], the patterns of peer influence they exhibit are surprisingly independent of their structure. On the other hand, when networks are very sparse, different network properties may contribute to enlarge the sphere of influence of each individual.…”
mentioning
confidence: 99%